Pengaruh Kepemimpinan dan Komitmen Terhadap Kinerja Karyawan dengan Kepuasan Kerja Sebagai Variabel Intervening Pada PT. Ans di Kota Padang - Hanifa Putri Alifa; Marta Widian Sari; Harmelia Harmelia (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This research aims to examine the magnitude of the influence of Leadership and Commitment on Employee Performance with Job Satisfaction as an intervening variable at PT. ANS in Padang City. The data collection method is through surveys and distributing questionnaires, with a sample of 56 respondents. The analytical method used is structural equation modeling using smartpls.The results of this research conclude that: (1) Leadership has a positive and significant effect on job satisfaction at PT. ANS in Padang City. (2) Commitment has a positive and significant effect on Job Satisfaction at PT. ANS in Padang City. (3) Leadership has a positive and significant effect on employee performance at PT. ANS in Padang City. (4) Commitment has a positive and significant effect on employee performance at PT. ANS in Padang City. (5) Job Satisfaction has a positive and significant influence on employee performance at PT. ANS in Padang City. (6) Leadership has a positive effect with significant value on employee performance through Job Satisfaction at PT. ANS in Padang City. (7). Commitment has a negative and significant effect on employee performance through Job Satisfaction at PT. ANS in Padang City.